RhoA Kinase Inhibition With Fasudil Versus Simvastatin in Murine Models of Cerebral Cavernous Malformations. Issue 1 (January 2017) - Shenkar, Robert; Shi, Changbin; Austin, Cecilia; Moore, Thomas; Lightle, Rhonda; Cao, Ying; Zhang, Lingjiao; Wu, Meijing; Zeineddine, Hussein A.; Girard, Romuald; McDonald, David A.; Rorrer, Autumn; et al.
Abstract : Background and Purpose—: We sought to compare the effect of chronic treatment with commonly tolerated doses of Fasudil, a specific RhoA kinase (ROCK) inhibitor, and simvastatin (with pleiotropic effects including ROCK inhibition) on cerebral cavernous malformation (CCM) genesis and maturation in 2 models that recapitulate the human disease. Methods—: Two heterozygous murine models, Ccm1 +/− Msh2 − /− and Ccm2 +/− Trp53 −/−, were treated from weaning to 4 to 5 months of age with Fasudil (100 mg/kg per day), simvastatin (40 mg/kg per day) or with placebo. Mouse brains were blindly assessed for CCM lesion burden, nonheme iron deposition (as a quantitative measure of chronic lesional hemorrhage), and ROCK activity. Results—: Fasudil, but not simvastatin, significantly decreased mature CCM lesion burden in Ccm1 +/− Msh2 −/− mice, and in meta-analysis of both models combined, when compared with mice receiving placebo. Fasudil and simvastatin both significantly decreased the integrated iron density per mature lesion area in Ccm1 +/− Msh2 −/− mice, and in both models combined, compared with mice given placebo. ROCK activity in mature lesions of Ccm1 +/− Msh2 −/− mice was similar with both treatments. Fasudil, but not simvastatin, improved survival in Ccm1 +/− Msh2 −/− mice. Fasudil and simvastatin treatment did not affect survival or lesion development significantly in Ccm2 +/− Trp53 −/− mice alone, and Fasudil benefit seemed limited to males. Conclusions—: ROCK inhibitor Fasudil was more efficacious than simvastatin in improving survival and blunting the development of mature CCM lesions. Both drugs significantly decreased chronic hemorrhage in CCM lesions. These findings justify the development of ROCK inhibitors and the clinical testing of commonly used statin agents in CCM. Abstract : Supplemental Digital Content is available in the text.